Linear immunoglobulin A bullous dermatosis induced by atezolizumab (Dermatology Reports, 2024)
Linear immunoglobulin A bullous dermatosis (LABD) is a rare immune-mediated vesiculobullous disease that is reported to be induced by infections or medications. Atezolizumab is a monoclonal antibody that targets programmed cell death ligand-1 and has been used to treat multiple cancers. Here, we report a case of drug induced LABD following the administration of atezolizumab.